Shelter for the urban poor in SANPASADA - Malaque III, Isidoro R. (Banwa, 2005)
With urbanization comes the problem of shelter provision for the urban poor in developing countries like the Philippines. The objective of this paper is to assess the socialized housing provision for the urban poor in the local government units of the Municipality of Sta. Cruz, Panabo City, Island Garden City of Samal, and Davao City (also known as SANPASADA). The assessment of the physical stock as an indicator includes the provision of land and the housing structure. The study shows that both local and national government units mostly assisted only in the lot acquisition of housing beneficiaries. The provision of housing structures was mostly provided through the initiative and ingenuity of the urban poor beneficiaries or with the assistance of the non-government organizations. Site development and the provision of infrastructure and utilities were done phase by phase through the initiative of the homeowners associations and from limited assistance of local government units. It is generally recommended that to promote a comprehensive approach in the provision of shelter needs of the urban poor, both the local and national government units should encourage the active participation and collaboration with NGOs and urban poor beneficiaries.